2018
DOI: 10.1021/acschembio.8b00556
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Novel EphA2 Agonistic Agents with Nanomolar Affinity in Vitro and in Cell

Abstract: EphA2 overexpression is invariably associated with poor prognosis and development of aggressive metastatic cancers in pancreatic, prostate, lung, ovarian, and breast cancers and melanoma. Recent efforts from our laboratories identified a number of agonistic peptides targeting the ligand-binding domain of the EphA2 receptor. The individual agents, however, were still relatively weak in affinities (micromolar range) that precluded detailed structural studies on the mode of action. Using a systematic optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(82 citation statements)
references
References 55 publications
4
78
0
Order By: Relevance
“…To determine whether the loss of the positive charge in the side chain of Lys 14 may contribute to the agonistic properties of the biotinylated peptides, we examined a version of ␤A-WLA-YRPK (16) with acetylation of the Lys 14 side chain ( Table 1, ␤A-WLA-YRPacK (21)). We found that the acetylated peptide has only slightly increased agonistic ability compared with ␤A-WLA-YRPK (16) (Fig. 4, E and G), suggesting that the Lys 14 positive charge has only minor detrimental effects on EphA2 activation.…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signalingmentioning
confidence: 87%
See 2 more Smart Citations
“…To determine whether the loss of the positive charge in the side chain of Lys 14 may contribute to the agonistic properties of the biotinylated peptides, we examined a version of ␤A-WLA-YRPK (16) with acetylation of the Lys 14 side chain ( Table 1, ␤A-WLA-YRPacK (21)). We found that the acetylated peptide has only slightly increased agonistic ability compared with ␤A-WLA-YRPK (16) (Fig. 4, E and G), suggesting that the Lys 14 positive charge has only minor detrimental effects on EphA2 activation.…”
Section: Nanomolar Peptides That Activate or Inhibit Epha2 Signalingmentioning
confidence: 87%
“…2A, compare ␤A-WLA-YR (15) with ␤A-WLA-Yam (9)). Because Arg 12 could introduce sensitivity to proteolytic degradation of C-terminal peptide extensions (16), we included a proline at position 13 because arginine followed by a proline is resistant to cleavage by trypsin-like proteases (16). We also included a lysine at position 14 to allow attachment of biotin or other tags (Table 1, ␤A-WLA-YRPK (16)).…”
Section: Modifications Increasing the Potency Of Ysa Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the dimerization of the receptor is a first critical event in the activation process, dimeric versions of the ephrinA1 ligand (ephrinA1-Fc), and of synthetic agonistic compounds (agent 135H12 [ 14 , 15 ] and Supplementary Table S1 ) were used as agents to probe the effect of EphA2 suppression in cellular and in vivo studies. Indeed, the ephrinA1 ligand is less effective as an agonist compared to the Fc dimerized molecule [ 16 ], and similarly, we recently reported that the synthetic agonistic agent 135H11 [ 14 , 15 ] is significantly less effective in activating the receptor in cellular assays than its dimeric version 135H12 [ 14 , 15 ]. The description of these agents, their affinity and selectivity for the EphA2-ligand binding domain, including biophysical characterization and X-ray structure in complex with EphA2, can be found in our recent publications [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Figure 1, the differences projected by several biphenyl rotational values are relatively modest, suggesting steric mimicry between these two groups, though the effective functional mimicry is very much dependent upon the actual biochemical settings [67]. In this context, the bioisosteric relationships between CF3 and i-Pr can be used for 2-amino-4,4,4-trifluorobutanoic acid 1 [68][69][70][71][72][73][74][75][76] substitution for leucine 2 in the de novo design of biologically active peptides and peptidomimetics [77][78][79][80][81][82][83]. As part of our ongoing research program focused on the application of fluorinated tailor-made AAs in pharmaceutical discovery, we needed a convenient access to large quantities of Fmoc-2amino-4,4,4-trifluorobutanoic acid 1 in both enantiomeric forms.…”
Section: Introductionmentioning
confidence: 99%